Regulation of Thyrotropin-Releasing Hormone-Expressing Neurons in Paraventricular Nucleus of the Hypothalamus by Signals of Adiposity - Ghamari-Langroudi, Masoud (The Endocrine Society, 2010)
Fasting-induced suppression of thyroid hormone levels is an adaptive response to reduce energy expenditure in both humans and mice. This suppression is mediated by the hypothalamic-pituitary-thyroid axis through a reduction in TRH levels expressed in neurons of the paraventricular nucleus of the hypothalamus (PVN). TRH gene expression is positively regulated by leptin. Whereas decreased leptin levels during fasting lead to a reduction in TRH gene expression, the mechanisms underlying this process are still unclear. Indeed, evidence exists that TRH neurons in the PVN are targeted by leptin indirectly via the arcuate nucleus, whereas correlative evidence for a direct action exists as well. Here we provide both in vivo and in vitro evidence that the activity of hypothalamic-pituitary-thyroid axis is regulated by both direct and indirect leptin regulation. We show that both leptin and α-MSH induce significant neuronal activity mediated through a postsynaptic mechanism in TRH-expressing neurons of PVN. Furthermore, we provide in vivo evidence indicating the contribution of each pathway in maintaining serum levels of thyroid hormone.